2018
DOI: 10.1186/s13756-018-0307-3
|View full text |Cite
|
Sign up to set email alerts
|

In vitro studies of the antibacterial activity of Copaifera spp. oleoresins, sodium hypochlorite, and peracetic acid against clinical and environmental isolates recovered from a hemodialysis unit

Abstract: BackgroundPatients submitted to hemodialysis therapy are more susceptible to infection, especially to infection by Gram-positive bacteria. Various research works have attempted to discover new antimicrobial agents from plant extracts and other natural products.MethodsThe present study aimed to assess the antibacterial activities of Copaifera duckei, C. reticulata, and C. oblongifolia oleoresins; sodium hypochlorite; and peracetic acid against clinical and environmental isolates recovered from a Hemodialysis Un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 70 publications
0
12
0
2
Order By: Relevance
“…In contrast, others concluded that PAA was able to significantly reduce L. monocytogenes from multispecies biofilms at 0.15% [32] and 0.3% [30], respectively. The MIC of PAA for other organisms seemed to be much lower, in the range of 0.01–0.03% for Gram-positive and Gram-negative flora isolated from citrus fruit [33], 0.0003% for Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa [34], and 0.0001–0.001% for P. aeruginosa , S. aureus , E. coli , and S. epidermidis [35]. Given the high tolerance of L. monocytogenes against PAA found in our data and by others, the ability of PAA to reduce L. monocytogenes from biofilms may primarily have been due to the elimination of the supporting flora in multispecies biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, others concluded that PAA was able to significantly reduce L. monocytogenes from multispecies biofilms at 0.15% [32] and 0.3% [30], respectively. The MIC of PAA for other organisms seemed to be much lower, in the range of 0.01–0.03% for Gram-positive and Gram-negative flora isolated from citrus fruit [33], 0.0003% for Escherichia coli, Staphylococcus aureus, Pseudomonas aeruginosa [34], and 0.0001–0.001% for P. aeruginosa , S. aureus , E. coli , and S. epidermidis [35]. Given the high tolerance of L. monocytogenes against PAA found in our data and by others, the ability of PAA to reduce L. monocytogenes from biofilms may primarily have been due to the elimination of the supporting flora in multispecies biofilms.…”
Section: Discussionmentioning
confidence: 99%
“…The viability of BeWo cells treated with different concentrations of oleoresins was assessed by MTT colorimetric assay 81 . In summary, we tested four oleoresins from different species from Copaifera genus as follows: the oleoresins of Copaifera reticulata, Copaifera duckei, Copaifera paupera, and Copaifera pubiflora were solubilized in dimethyl sulfoxide (DMSO) and diluted in supplemented RPMI 1,640 medium to form a stock solution of 640 µg/mL 51,82 . BeWo cells were seeded at 3.0 × 10 4 cells/well in 96-well microplates.…”
Section: Methodsmentioning
confidence: 99%
“…Their oleoresins are obtained by tapping the trunk of trees and have been extensively studied because of its medicinal properties 49 . These oleoresins exhibit remarkable biological properties such as antimicrobial, anti-inflammatory, and antiparasitic activity [49][50][51][52][53] . However, no current studies investigated the impact of oleoresins from Copaifera genus in T. gondii infection.…”
mentioning
confidence: 99%
“…In relation to the various Copaifera species chemical composition, UPLC-MS/MS and CG/MS analyses of the oleoresins have identified acid diterpenes and major volatile sesquiterpenes, whereas high contents of phenolic compounds including flavonoid heterosides and galloylquinic acid derivatives have been verified in the leaves [30]. Among the oleoresin constituents, diterpenes are by far the main components and include ent -agathic acid, ent -copalic acid, and ent -kaurenoic acid, followed by sesquiterpenes like β -bisabolene, α -humulene, and trans- β -caryophyllene [30, 48]. In the case of Copaifera species leaf hydroalcoholic extracts, they contain mainly quercetin, afzelin, and quinic acids [30].…”
Section: Discussionmentioning
confidence: 99%